Antimicrobial Activity of Basil (Ocimum basilicum L.) Against Gram-Negative Bacteria Involved in Pneumonia Infection - Sulistiyawati, Indah; Falah, Muhammad; Anggraeni, Gita; Rovik, Anwar (JST (Jurnal Sains dan Teknologi), 2023)
Infectious diseases are still a global problem, for example, acute respiratory infections (SARI). Resistance in pneumonia involving Gram-negative bacterial infection reduces the effectiveness of antibiotic use and increases the length of hospital stay. This study examines the potential of antimicrobial compounds from basil plants against isolates of Gram-negative bacteria involved in pneumonia infection. This research is an experimental study through several stages: basil extraction, initial screening of bioactive compounds, isolation and identification of bacteria from sputum, and testing for antimicrobial activity of basil extracts. Sputum samples were collected from 43 pneumonia patients (male and female) involving Klebsiella pneumoniae, Acinetobacter baumannii, Enterobacter aerogenes, Pseudomonas aeruginosa, Serratia marcescens, Proteus mirabilis, and Escherichia coli. The inhibitory activity against pathogenic bacteria was directly proportional to the basil extract concentration. Initial screening for phytochemical compounds showed that the extracts of basil leaves and stems contained active compounds of tannins and flavonoids. The 25% concentration of basil extract was the minimum inhibitory concentration (MIC) against the test bacteria. The 100% basil extract concentration produced the largest inhibition zone i.e., 10.93 mm. The overall findings of this study provide baseline information for the possible use of the Ocimum basilicum extract in the treatment of pneumonia involving Gram-negative bacteria.